Sosialisasi Pemanfaatan Buah Kedabu Menjadi Produk Olahan Sirup di Kabupaten Kepulauan Meranti - Meldra, Delia; Mardiansyah, Yopy (LPPM ITEBA, 2025)
The Meranti Islands Regency is an archipelago surrounded by water, so the islands are surrounded by mangrove trees, better known as kedabu trees by the local community. Kedabu fruit is simply left to ripen on the tree and fall into the water, so efforts are needed to utilize the fruit. This outreach activity aims to provide knowledge to the community about the benefits and how to process kedabu fruit into a refreshing syrup with its sour taste, encourage kedabu fruit processing, teach logo creation with Canva, and recommend suggestions for processing development. The method or approach used in this activity is a participatory approach. This approach is a practice of communicative, transactive, advocacy, and collaborative planning theory. This training activity received a positive response and interest in continuing the process of processing kedabu fruit into other processed products, such as Kedabu dodol. It is recommended that future activities include a mentoring program that provides solutions and support regarding product marketing, PIRT, and so on.